PRIORITY SCIENTIFIC APPROACHES AND INNOVATIONS IN MANAGING PRODUCTION RESOURCES IN COTTON-TEXTILE CLUSTERS (Marketing Journal, 2025)
This study analyzes advanced approaches to inventory management in cotton - textile clusters. It explores the implementation of ERP systems, artificial intelligence, digital logistics, and automated warehouse technologies for real-time inventory control. The significance of human capital and the need for continuous training are emphasized. Based on the analysis, practical recommendations are proposed to enhance cluster efficiency.
Keywords: cotton -textile cluster; inventory management; digital logistics; artificial intelligence; ERP system; automation; human capital